Continuing Education for the Emerging Social Work Profession in China: The Experiment in Shenzhen. Issue 4 (7th August 2016) - Lam, Ching Man; Yan, Miu Chung; Liang, Yan
ABSTRACT: In-service training as a form of continuing professional education (CPE) is important for social work professionals to maintain their skills and enhance their knowledge for publicly accountable practice. These goals are concerns in Mainland China, which has experienced rapid development in social work since economic reforms started in the early 1980s. This article reports the findings of a qualitative study that explored the in-service training experience of 36 social workers in the major city of Shenzhen, an "important role model" for social work development in China. The findings reveal that participants expect in-service training to be practical and applicable, and their narrative accounts reveal first a disconnect between their needs and the in-service training provided, and second their quest for value-based training to sustain their commitment to the social work profession. To strengthen CPE for social workers in China, a more consultative, flexible, and customized approach, as well as an experiential learning model, are needed. In light of these findings, the authors discuss the role and functions of CPE in a China-specific context and reflect on how CPE can be better delivered to meet the needs of current social workers in China.